Using vaginal temperature to evaluate heat stress in dairy cattle - Cvetkovic, B.; Smith, John F., 1962-; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A rise in body temperature is a signal that heat stress has exceeded the heat-exchange capacity of the dairy cow. Previous studies have shown a strong positive correlation between vaginal temperature and respiration rate, demonstrating a stress response to an increased body temperature. Vaginal temperature was collected by using temperature probes attached to an external data logger. Although these devices were very sensitive to changes in body temperature of cows housed in tie-stalls, the external data logger presented a significant application challenge for freeranging animals housed in freestalls. A data logger was acquired that would be completely indwelling in the vagina. The U12 stainless steel model (Onset Computer Corporation, Pocasset, MA) was 0.5 × 4 inches and weighed about 2.6 oz. It was retained in the vagina with foam and a blank CIDR insert. These devices were used continuously to measure and record body temperature in freeranging cattle for 5 to 7 days. Vaginal temperature was recorded at 1-minute intervals and then averaged into 5-minute blocks. Data were then graphed over a 24-hour period. Vaginal temperature increased with activity and amount of heat stress. Effective heatabatement systems were shown to reduce vaginal temperature. On commercial farms, data were used to identify where heat abatement should be improved. Heat stress issues with milking parlor holding pens were easily identified. Producers and industry personnel could use data loggers to evaluate heat stress and the effectiveness of heat-abatement systems on free-ranging dairy cattle. Devices also could be used to validate the effectiveness of modifications to heat-abatement systems identified by the initial evaluation.
Dairy Research, 2005 is known as Dairy Day, 2005
Keywords: Dairy; Cow comfort; Cow cooling; Heat abatement